Highly Conductive Ti3C2Tx MXene Hybrid Fibers for Flexible and Elastic Fiber‐Shaped Supercapacitors. Issue 8 (17th January 2019) - Zhang, Jizhen; Seyedin, Shayan; Qin, Si; Wang, Zhiyu; Moradi, Sepehr; Yang, Fangli; Lynch, Peter A.; Yang, Wenrong; Liu, Jingquan; Wang, Xungai; Razal, Joselito M.
Abstract: Fiber‐shaped supercapacitors (FSCs) are promising energy storage solutions for powering miniaturized or wearable electronics. However, the scalable fabrication of fiber electrodes with high electrical conductivity and excellent energy storage performance for use in FSCs remains a challenge. Here, an easily scalable one‐step wet‐spinning approach is reported to fabricate highly conductive fibers using hybrid formulations of Ti3 C2 T x MXene nanosheets and poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate. This approach produces fibers with a record conductivity of ≈1489 S cm −1, which is about five times higher than other reported Ti3 C2 T x MXene‐based fibers (up to ≈290 S cm −1 ). The hybrid fiber at ≈70 wt% MXene shows a high volumetric capacitance (≈614.5 F cm −3 at 5 mV s −1 ) and an excellent rate performance (≈375.2 F cm −3 at 1000 mV s −1 ). When assembled into a free‐standing FSC, the energy and power densities of the device reach ≈7.13 Wh cm −3 and ≈8249 mW cm −3, respectively. The excellent strength and flexibility of the hybrid fibers allow them to be wrapped on a silicone elastomer fiber to achieve an elastic FSC with 96% capacitance retention when cyclically stretched to 100% strain. This work demonstrates the potential of MXene‐based fiber electrodes and their scalable production for fiber‐based energy storage applications. Abstract : Highly electrical conducting MXene‐based fiber is fabricated by easily scalable one‐step wet‐spinning, using hybrid formulations of Ti3 C2 T x MXene nanosheets and poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate. MXene‐based fibers show a record conductivity of ≈1489 S cm −1 and high volumetric capacitance (≈614.5 F cm −3 ), which demonstrates the potential of MXene‐based fiber electrodes and its scalable production for fiber‐based energy storage applications.